2007
DOI: 10.1111/j.1570-7458.2007.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone of the larch caterpillar moth, Dendrolimus superans, from northeastern China

Abstract: The larch caterpillar moth, Dendrolimus superans Butler (Lepidoptera: Lasiocampidae), is a serious pest in the northeastern part of China. In order to develop an effective method for monitoring D . superans , we began a project to identify the sex pheromone of D . superans and preliminary results were published in a note in 2001. Here we report complete laboratory and field results to support the identification. ( Z , E )-5,7-Dodecadienal, ( Z , E )-5,7-dodecadienol, ( Z )-5-dodecenol, and ( Z )-5-dodecenal (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition, the antennae of male D. tabulaeformis responded to synthetic Z 5, E 7-12:Ald and E 5, Z 7-12:Ald in our GC-EAD analyses, but the two compounds were not detected in pheromone gland extracts. It has been reported that the sex pheromones of D. superans and D. houi consist of Z 5, E 7-12:Ald [7] and E 5, Z 7-12:Ald [9] , respectively. Dendrolimus tabulaeformis is broadly sympatric with D. superans in Inner Mongolia, He'bei, and Liao'ning, and sympatric with D. houi in Shăn'xi and Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antennae of male D. tabulaeformis responded to synthetic Z 5, E 7-12:Ald and E 5, Z 7-12:Ald in our GC-EAD analyses, but the two compounds were not detected in pheromone gland extracts. It has been reported that the sex pheromones of D. superans and D. houi consist of Z 5, E 7-12:Ald [7] and E 5, Z 7-12:Ald [9] , respectively. Dendrolimus tabulaeformis is broadly sympatric with D. superans in Inner Mongolia, He'bei, and Liao'ning, and sympatric with D. houi in Shăn'xi and Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the derivatives of (5Z,7E)-and (5E,7Z)-dodecadienol are the active sex pheromone components of pine caterpillars. [30][31][32][33] In addition, (11Z,13Z)-hexadecadienal, together with related derivatives, are the critical sex pheromones and attractants in Notodonfidae. 18,34 (8E,10E)dodecadienyl acetate synergizes the codlemone attraction to male Cydia pomonella, and it is also the sex pheromone of Cydia toreuta (Grote) and Melissopus latiferreanus.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Samples Pheromone extracts were prepared as described previously (Kong et al, 2007a, b). Briefly, individual female sex pheromone glands were excised during the peak period of calling (0-2 d-old, 4-7 h into the scotophase) and extracted about 30 min in redistilled hexane (10 μl per gland).…”
Section: Methodsmentioning
confidence: 99%
“…So far, sex pheromones have been reported for the masson pine caterpillar moth, D. punctatus (Zhao et al, 1993), the pine moth, D. spectabilis (Ando et al, 1982;Kong et al, 2003), the larch caterpillar moth, D. superans (Klun et al, 2000;Kong et al, 2007a), the Yunnan pine caterpillar moth, D. houi (Kong et al, 2007b), and the European pine moth D. pini (Priesner et al, 1984;Kovalev et al, 1993). Sex pheromones components that have been identified from Dendrolimus species are all (5Z,7E)-5,7-dodecadienes with different terminal functional groups (alcohol, acetate, propionate, and aldehyde), except for the sex pheromone of D. houi, which was reported as a mixture of (5E,7Z)-5,7-dodecadien-1-yl acetate (E5,Z7-12:OAc), (5E,7Z)-5,7-dodecadien-1-ol (E5,Z7-12:OH), and (5E,7Z)-5,7-dodecadienal (E5,Z7-12:Ald) (Kong et al, 2007b).…”
Section: Introductionmentioning
confidence: 97%